KEANEKARAGAMAN BURUNG MIGRAN DI PESISIR PANTAI TIMUR KABUPATEN DELI SERDANG SUMATERA UTARA - Desi Yani Harahap; Pindi Patana; Rahmawaty Rahmawaty (Peronema Forestry Science Journal, 2013)
Mudflat and mangrove ecosystem both are the migratory bird habitat. This research was  counting  the index of diversity migratory shorebirds East Coastal of Deli Serdang District, Province of North Sumatra. The result showed  value average  an index of diversity  with medium category (H' 2.03). The highest diversity (H' = 2.12) was found at Bagan Percut and the lowest (H' = 1.94) found at Pantai Ancol. Included in medium category, the diversity of migratory shorebirds influenced by mudflat condition. Keywords: mudflat, migratory birds, mangrove, coastal area.